Karyologic diversification and phylogenetic relationships of the genus Thalpomys (Rodentia, Sigmiodontinae) - de Andrade, AFB; Bonvicino, C. R.; Briani, D. C.; Kasahara, S. (Springer, 2004)
We describe the karyotype of Thalpomys species, from different Brazilian localities of the Cerrado. Thalpomys cerradensis Herskovitz, 1990 showed 2n = 36, FN = 34 and T. lasiotis Thomas, .1916 2n = 38, FN = 38. Comparisons of G-band karyotypes showed evident inter-specific homologies indicating that their chromosome complements could be derived from one another by two presumed rearrangements. Both species showed pericentromeric C-band regions in almost all chromosomes but a comparison with CMA3/DA/DAPI staining indicated that the molecular content of heterochromatic regions was different. T. lasiotis specimens from two different localities differed in the morphology of the X chromosome due to the presence of a short heterochromatic arm. These chromosome types are apparently fixed in each population rather than maintained as a polymorphic variation. Phylogenetic analyses supported the monophyly of the genus Thalpomys but was not capable of elucidating its phylogenetic relationship to other Akodontini rodents. These analyses also showed inter-individual variation in T. lasiotis, even within a given population. Phylogenetic analyses placed T. lasiotis specimens with different karyotypes in different monophyletic branches. Molecular and karyologic data confirmed the identity of the genus Thalpomys.
Keywords: Rodentia; Thalpomys; karyotype; phylogeny; distribution; Brazil